Penguatan Penguasaan Kosakata Bahasa Inggris Bagi Kelompok Kerja Guru PJOK Talo Induk dan Ilir Talo di Kabupaten Seluma - Febrianti, Mariska; Putra, Aziiz Rahman; Hidayat, Ilham; Trigono, Rahmat (Institut Teknologi Pendidikan Indonesia, 2024)
The world of sports is closely related to English, where PJOK teachers are currently encouraged to be more creative and innovative so that students' knowledge and skills can develop optimally, even when they are in elementary school, one of which is mastering related English terms. with English. sport. Unfortunately, there are still many PJOK teachers who make mistakes in pronouncing several sports terms even though the vocabulary is actually already common among the public and even has familiar meanings. The UNIVED Bengkulu Physical Education PKM Team provided activities to strengthen mastery of English vocabulary to the Teacher Working Group (KKG) of PJOK Talo Induk and Ilir Talo Seluma Regency at SDN 09 Seluma with the aim of correcting pronunciation errors and increasing the capacity and quality of the English language. PJOK teacher regarding the use of English vocabulary. English that will be used in learning for elementary school students. This service activity brought benefits to the PJOK Talo Induk and Ilir Talo Teacher Working Groups of Seluma Regency in improving their pronunciation and mastery of English vocabulary regarding sports terms. Through this activity, participants, namely PJOK teachers, were able to understand the meaning of English terms in sports. The results of receiving benefits from community service can be seen from the enthusiasm of the participants during the activity, namely being active and responding positively to the material presented by the service team.